Rancang Bangun Aplikasi Tes IELTS Online Berbasis Web Dengan Penilaian Otomatis Pada Lembaga Bahasa Asc Indonesia - Wandi Aprianto (GLOBAL SCIENTS PUBLISHER, 2025)
English language proficiency is a crucial competency in both academic and professional environments. One of the most widely used instruments to assess this proficiency is the International English Language Testing System (IELTS). However, conventional test administration still faces several challenges, such as time-consuming scoring processes and inefficient administrative management. Therefore, this study aims to design and develop a web-based IELTS testing application with an automated scoring system at the ASC Indonesia Language Institute. The development of this application employs the waterfall method, which consists of requirements analysis, system design, implementation, and maintenance stages. The technologies used include the Laravel framework for the backend, Vue.js for the frontend, and MySQL as the database management system. The automated scoring system is implemented using a rule-based algorithm aligned with IELTS scoring standards. The testing results indicate that the developed application is capable of supporting IELTS test administration in a more effective and efficient manner. The scoring process can be performed automatically with a high level of speed and accuracy. In addition, the application provides test result reporting features that assist both test participants and language institute administrators in evaluating and analyzing English language proficiency. In conclusion, this web-based IELTS testing application is expected to serve as an innovative digital solution to enhance the quality and efficiency of English language test administration.